Management of polyostotic eosinophilic granuloma - Ajay Parihar; Vilas Newaskar (Wolters Kluwer Medknow Publications, 2012)
Eosinophilic granuloma is a rare disease which is difficult to diagnose clinically and radiographically. Localized Langerhans' cell histiocytosis, previously known as eosinophilic granuloma, mainly affects the skull, mandible, vertebrae, pelvis and ribs in children and the long bones of adults. We present a case report of a female who developed pain and swelling over the left mandibular region, and was later diagnosed as eosinophilic granuloma, which after administration of intralesional corticosteroid with surgical enucleation showed positive response. This disease is of importance to dental professionals because early clinical signs can occur in the jaw and can cause extensive destruction of the periodontal tissues and bone. The purpose of this case report is to describe a case of eosinophilic granuloma with emphasis on conservative approach for the treatment and the radiographic changes observed during and after the treatment.